Mudra: Micro Units Development and Refinance Agency: Improving Financial Inclusion for Non-Corporate Small Businesses in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Non –Corporate Small Business Sector (NCSBS) is the economic foundation of India. It plays a very important role in the socio- economic development of the country. In past six decades it has significantly contributed to the growth of GDP (Gross Domestic Product), foreign trade and employment generation. Therefore the performance of this sector has a direct impact on the overall growth of the economy. According to the survey by NSSO (2013), there are 5.77 cr. Micro small scale units, engaging around 12 cr. People, mostly own account enterprises or solitary proprietorships in the country. Above 60 of units are owned by SC, ST, and other backward classes. They are unaware about credit, insurance, loan and other financial services and generally depend on local lenders who grant them money on very lofty interest rates. Shortage of sufficient financial resources is the major problem facing by these sectors, to improve this weaker section our honorable Prime Minister launched the promised Micro Units Development and Refinance Agency (MUDRA) Yojana to facilitate those people, small institutions who are not capable to start their business self. This paper mainly concerned with an overview on purpose of assistance, eligible borrowers, promoters contributions, upfront fee, security and tenor of assistance.